Analisis kestabilan lubang bukaan menggunakan q-system pada penambangan bawah tanah PT.Cahaya Bumi Perdana Sawahlunto - dinda apriko harli; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2023)
A mining method where all activities are carried out below the earth's surface is called underground mining. Underground mining activities can cause collapses, to prevent this from happening by analyzing the stability of openings using the Q-System method. The parameters used to find the Q value are rock quality designation, joint set number, joint roughness, joint alteration number, stress reduction factor. Look for the value of the tunnel safety factor and also the value of the meanstress acting on the tunnel BT-03 Value the tunnel and also the voltage acting on the BT-03 tunnel using phase2 software. The results obtained include the Q-System value for coal is 1.8 and sandstone is 1.6, The tunnel safety factor value is 0.9, which means the tunnel is in an unstable condition so it is necessary to install supports.The minimum voltage value working on tunnel BT-03 is 2.00 while the maximum voltage is 3.50.